Single nucleotide polymorphisms minisequencing in hypervariable regions for screening of Thais - Thongngam P. (2017)
© 2017 Elsevier B.V. Mitochondrial DNA (mtDNA) analysis has displayed an important role and been considered as a powerful tool in various fields of forensic science applications. Nowadays, single nucleotide polymorphisms (SNPs) on mtDNA have become additional DNA markers when conventional STR typing practically fails. mtDNA sequencing of polymerase chain reaction (PCR) products from the hypervariable region I (HVRI) and II (HVRII) is the standard method of mtDNA analysis. However, mtDNA sequencing is rather expensive, time consuming and technically complex. This study aims to develop the SNPs minisequencing for screening of Thai populations. For this purpose, sixteen SNPs that possess high discriminating power in hypervariable regions were selected. The DNA samples were obtained from 100 buccal swab samples of Thai healthy individuals. All DNA samples were extracted and were subsequently amplified by single duplex PCR technique. The duplex PCR products were genotyped by SNPs minisequencing. Based on 16 SNPs, a total of 63 haplotypes were observed of which 46 haplotypes were unique. The haplotype diversity, discriminating power and random match probability were calculated to be 0.9830, 0.9732 and 0.0268, respectively. The SNPs at 150, 199, 489, 16129, 16189, 16223, and 16304 were highly polymorphic in the studied population. Our results suggested that the SNPs minisequencing can be an alternative method of SNPs genotyping. This method can be used for an exclusion of a large number of mismatch samples and as a presumptive test prior to do confirmatory mtDNA sequencing.